Risk Factor for Relapse in Childhood Nephrotic Syndrome - A Hospital Based Retrospective Study - Sarker, MN; Islam, MMSU; Saad, T; Shoma, FN; Sharmin, LS; Khan, HA; Afrooz, F; Fatmi, LE; Alam, A; Salimullah, ASM; et al. (Faridpur Medical College Journal, 2012)
Nephrotic Syndrome (NS) is a common childhood illness characterized by massive proteinuria, hyperlipidemia, hypoalbuminemia & edema. NS is a disease of relapse and it is a major problem to manage the cases with frequent relapse. So it is very important to find out such children who are prone to develop frequent relapse. This retrospective study was conducted in the paediatric department of Dhaka Medical College Hospital (DMCH) from January to December 2005.Total 100 children with relapsed NS of them 50 had Frequent Relapse NS (FRNS) and 50 had Infrequent Relapse NS (IFRNS) were included in the study with a view to find out the risk factors for relapse. Data were collected from previous medical and hospital records. Data were analyzed by using SPSS program. Chi-squared test and Student's t-Test were used as statistical test and p value < 0.05 was taken as significant. NS was more common among 2-6 years of age (67%) with male to female ratio roughly 2:1. Most of patient with frequent relapse had age <5 years, came from rural area and belongs to poor social class compared to that of infrequent relapse. The mean age at first onset was significantly less in frequent relapse group than that of infrequent relapse group. Majority of atopic child belongs to frequent relapse cases. Low serum albumin level, low serum total protein level, culture positive Urinary Tract Infection (UTI) at initial attack were observed to be statistically significant in case of frequent relapse group. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10292 Faridpur Med. Coll. J. 2012;7(1): 18-22